Cauchy–Maxwell equations: A space–time conformal gauge theory for coupled electromagnetism and elasticity. (November 2020) - Roy, Pranesh; Kumar, Sanjeev; Roy, Debasish
Abstract: A space–time conformal gauge theory is used to develop a unified continuum model describing myriad electromechanical and magnetomechanical coupling effects observed in solids. Using the pseudo-Riemannian Minkowski metric in a finite-deformation setup and exploiting the Lagrangian's local conformal symmetry, we derive Cauchy–Maxwell (CM) equations that seamlessly combine, for the first time, Cauchy's elasto-dynamic equations with Maxwell's equations for electromagnetism. Maxwell's equations for vacuum are recoverable from our model, which in itself also constitutes a new derivation of these equations. With deformation gradient and material velocity coupled in the Lagrange density, various pseudo-forces appear in the Euler–Lagrange equations. These forces, not identifiable through classical continuum mechanics, should have significance under specific geometric or loading conditions. As a limited illustration on how the CM equations work, we carry out semi-analytical studies, viz. on an infinite body subject to isochoric deformation and a finite membrane under both tensile and transverse loading, considering piezoelectricity and piezomagnetism. Our results show that under specific loading frequencies and tension, electric and magnetic potentials may increase rapidly in some regions of the membrane. Explorations of this nature via the CM model may have implications in future studies on efficient energy harvesting. Highlights: A space-time conformal gauge theory is used to unify myriad electromechanical and magnetomechanical coupling effects observed in solids. Derivation of Cauchy-Maxwell (CM) equations exploiting local conformal symmetry of the Lagrangian. A new derivation of Maxwell's equations for vacuum is obtained as a special case. Coupling of deformation gradient and material velocity leading to modifications of momentum. Semi-analytical studies are carried out on an infinite body subject to isochoric deformation and a finite membrane under both tensile and transverse loading, considering both piezoelectricity and piezomagnetism.